Risk Factors of Cage Subsidence in Patients Received Minimally Invasive Transforaminal Lumbar Interbody Fusion - Yao, Yu-Cheng; Chou, Po-Hsin; Lin, Hsi-Hsien; Wang, Shih-Tien; Liu, Chien-Lin; Chang, Ming-Chau (Spine (Philadelphia, Pa. 1976), 2020)
A retrospective cohort study. To determine the risk factors of cage subsidence in patients undergoing minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) and its correlation with patient-reported outcomes. Cage subsidence is among the cage-related complications after TLIF and may lead to poor outcomes. Few studies have addressed the incidence of cage subsidence in MI-TLIF. This retrospective study of a prospectively collected database was conducted from October 2015 to October 2017. All patients received MI-TLIF with a minimum of 2-year follow-up. All levels were separated into the cage subsidence (CS group) and no cage subsidence (non-CS group) groups. Cage subsidence was evaluated using lateral radiographs and defined as more than 2 mm migration of the cage into the endplate of adjacent vertebral body. Patient demographics, perioperative details, and radiographic parameters were recorded. Cage-related parameters were cage height, cage insertion level, and cage position. Cage position was recorded using central point ration (CPR). Patient-reported outcome was analyzed using the Oswestry Disability Index (ODI) questionnaire and Visual Analog Scale (VAS) preoperatively and at 2 years postoperatively. Ninety-three patients (126 levels) were included. Mean age was 66.5 years with an average follow-up of 36.9 months. Overall incidence of cage subsidence was 34.1%. The CS group had significantly higher body mass index, less bone mineral density (BMD), shorter disc height, and higher CPR than the non-CS group. BMD, disc height, and CPR were significantly negatively correlated with depth of cage subsidence. ODI improvement was significantly lesser in the CS group than in the non-CS group. Fusion rate and complications were unrelated to cage subsidence. The BMD, disc height, and cage position were the most significant risk factors that were negatively correlated with depth of cage subsidence. Placing a TLIF cage anteriorly if possible may reduce the risk of cage subsidence. 3.